2019
DOI: 10.1055/s-0039-1696963
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implants and Radiation

Abstract: One of the most influential factors in the success of breast reconstruction is whether or not radiation therapy has or will be performed. While traditional teaching is that all breasts treated with radiation therapy must be reconstructed with an autologous component, many reconstructive surgeons perform implant-based breast reconstruction without an autologous component and have success doing so. The purpose of this article is to explore the risks, benefits, and nuances of performing implant-based breast recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
4
1
Order By: Relevance
“…Another study by Reinders et al (mean follow-up: 21.75 months) reported an occurrence rate of Baker III-IV capsular fibrosis of 13/80 patients (16.9%) with a 13% rate of surgical revision, which is considerably lower than in our current study [8]. Nava et al reported in 109 patients (median follow-up: 50 months) a higher rate of capsular contracture of 57.8% without further differentiation regarding Baker classification; however, a considerably lower reconstructive failure rate of only 6.4% was detected [22,23]. It is widely accepted that PMRT following breast reconstruction is associated with an increased risk of secondary breast reconstruction surgery [24].…”
Section: Discussioncontrasting
confidence: 72%
“…Another study by Reinders et al (mean follow-up: 21.75 months) reported an occurrence rate of Baker III-IV capsular fibrosis of 13/80 patients (16.9%) with a 13% rate of surgical revision, which is considerably lower than in our current study [8]. Nava et al reported in 109 patients (median follow-up: 50 months) a higher rate of capsular contracture of 57.8% without further differentiation regarding Baker classification; however, a considerably lower reconstructive failure rate of only 6.4% was detected [22,23]. It is widely accepted that PMRT following breast reconstruction is associated with an increased risk of secondary breast reconstruction surgery [24].…”
Section: Discussioncontrasting
confidence: 72%
“…Regarding immediate autologous reconstruction, they also have controversial results, but are shown to be less severe than immediate reconstructions with silicone implants (36) . Dewael et al (2019) 33 evaluated late complications in patients who performed immediate autologous reconstruction compared to patients who performed late (post-radiotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding immediate autologous reconstruction, they also have controversial results, but are shown to be less severe than immediate reconstructions with silicone implants. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation in the patient’s oncologic care is a well-known and well-studied risk factor for increased complications and reconstructive failure [ 5 , 6 ]. Since the appropriate management of cancer frequently requires radiation treatment (RT) to improve survival and recurrence rates, it is incumbent on the reconstructive surgeon to identify and implement strategies to compensate for this therapy.…”
Section: Introductionmentioning
confidence: 99%